IMPLEMENTASI PROGRAM PEMBANGUNAN INFRASTRUKTUR KELURAHAN DI KECAMATAN SUMEDANG UTARA KABUPATEN SUMEDANG - Ahmad Almutii Lillah (JRPA - Journal of Regional Public Administration, 2026)
Infrastructure development is essential for community welfare and national economic growth, serving as a long-term investment. This study aims to examine the implementation of the Urban Infrastructure Development Program in Sumedang Utara District, Sumedang Regency. The research uses a qualitative approach, focusing on the dimensions of designed policy, resources, community participation, and involved actors. Informants were selected through purposive sampling, including the Head of Development and Community Empowerment at the district level, Heads of Development in Kotakaler and Situ Urban Villages, and the Community Empowerment Institution (LPM). Data collection techniques included observation, interviews, documentation, and triangulation. Data validity was tested through credibility, transferability, dependability, and confirmability. Data analysis was carried out through data collection, reduction, display, and verification. The findings indicate that the program implementation has been fairly effective, marked by policy clarity, program relevance, and growing community participation. The support of resources and simple technology further strengthens implementation. However, challenges remain, such as uneven information dissemination, limited understanding of policies, and suboptimal task distribution. Coordination among actors and capacity building for implementers are key areas that need continuous improvement.